Biological and chemical Study to evaluate the types of water used for drinking in the Al-youssiffiyah area and its effect on public health (Baghdad Science Journal, 2009)
Election study included four sites for the waters in area of Youssifiyah south of Baghdad (river water, tank water, liquefactions water, and water filtrate and seethed and purifier by alum and chloride), the samples were collected during the month of June in 2007. Temperature, electrical conductivity and acidity are measured. Also , the concentration of chloride , sulphate , carbonate , nitrate , sodium , calcium , magnesium , hard total and total dissolved substances are determined , as well as heavy metals assess environmental risk (such as Cu, Pb, Zn, Fe). It was also a study of bacterial totals included both total Bacteria (TB) and Total Coliform Bacteria (TC) and Fecal Coliform (FC) and Fecal Streptococci (FS). The study showed the increased values of electrical conductivity of water river, which ranged between (655 – 805) µs. cm-1 and increasing of total dissolved substances and the sodium and chloride, which ranged between (193 - 195) mg / L, (890 - 1200), (148 -- 155) mg / L, respectively, because of the use of al-shab and chlorine in the process of liquidation, which led to a decrease in the amount of the total suspends substances in all samples. Found high levels of iron in all the samples because of the deteriorating pipes liquidation, and that all the measurements fall within acceptable limits for the measurements of the specifications of the Iraq. While the results of Diagnostic bacteria showed that the highest values of bacterial totals were in the liquefaction that led to the emergence of cases of diarrhea and inflammation of urinary sewage when some residents of this region, these results agree with the statistical medical center's health in the region.